Answer: 4
<u>Explanation:</u>
f(x) = 2x - 1
f(√2) = 2√2 - 1
f(1) = 2(1) - 1
= 2 - 1
= 1
f(√3) = 2√3 - 1
*******************************************************
![\frac{f(\sqrt{2})-f(1)}{\sqrt{2}-1} +\frac{f(\sqrt{3})-f(\sqrt{2})}{\sqrt{3}-\sqrt{2}}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28%5Csqrt%7B2%7D%29-f%281%29%7D%7B%5Csqrt%7B2%7D-1%7D%20%2B%5Cfrac%7Bf%28%5Csqrt%7B3%7D%29-f%28%5Csqrt%7B2%7D%29%7D%7B%5Csqrt%7B3%7D-%5Csqrt%7B2%7D%7D)
= ![\frac{(2\sqrt{2}-1)-1}{\sqrt{2}-1} +\frac{(2\sqrt{3}-1)-(2\sqrt{2}-1)}{\sqrt{3}-\sqrt{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B%282%5Csqrt%7B2%7D-1%29-1%7D%7B%5Csqrt%7B2%7D-1%7D%20%2B%5Cfrac%7B%282%5Csqrt%7B3%7D-1%29-%282%5Csqrt%7B2%7D-1%29%7D%7B%5Csqrt%7B3%7D-%5Csqrt%7B2%7D%7D)
= ![\frac{2\sqrt{2}-2}{\sqrt{2}-1} +\frac{2\sqrt{3}-2\sqrt{2}}{\sqrt{3}-\sqrt{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Csqrt%7B2%7D-2%7D%7B%5Csqrt%7B2%7D-1%7D%20%2B%5Cfrac%7B2%5Csqrt%7B3%7D-2%5Csqrt%7B2%7D%7D%7B%5Csqrt%7B3%7D-%5Csqrt%7B2%7D%7D)
= ![\frac{2\sqrt{2}-2}{\sqrt{2}-1}(\frac{\sqrt{2}+1}{\sqrt{2}+1})+\frac{2\sqrt{3}-2\sqrt{2}}{\sqrt{3}-\sqrt{2}}(\frac{\sqrt{3}+\sqrt{2}}{\sqrt{3}+\sqrt{2}})](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Csqrt%7B2%7D-2%7D%7B%5Csqrt%7B2%7D-1%7D%28%5Cfrac%7B%5Csqrt%7B2%7D%2B1%7D%7B%5Csqrt%7B2%7D%2B1%7D%29%2B%5Cfrac%7B2%5Csqrt%7B3%7D-2%5Csqrt%7B2%7D%7D%7B%5Csqrt%7B3%7D-%5Csqrt%7B2%7D%7D%28%5Cfrac%7B%5Csqrt%7B3%7D%2B%5Csqrt%7B2%7D%7D%7B%5Csqrt%7B3%7D%2B%5Csqrt%7B2%7D%7D%29)
= ![\frac{4+2\sqrt{2}-2\sqrt{2}-2}{2 - 1} + \frac{6 +2\sqrt{6}-2\sqrt{6}-4}{3-2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%2B2%5Csqrt%7B2%7D-2%5Csqrt%7B2%7D-2%7D%7B2%20-%201%7D%20%2B%20%5Cfrac%7B6%20%2B2%5Csqrt%7B6%7D-2%5Csqrt%7B6%7D-4%7D%7B3-2%7D)
= ![\frac{2}{1} +\frac{2}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B1%7D%20%2B%5Cfrac%7B2%7D%7B1%7D)
= 4
Answer:
Both equations are same
Step-by-step explanation:
The reason why this is true is not far fetched
looking at the first equation, we have;
3-x = 4
we can also factorize the second equation to look this way
By this, we shall be having
3(4) = 3(3-x)
By the time we take out the 3 from both sides, we will have the initial equation
So what we are saying is that both equations are the same
2? bc if x=7 then it equals 2(7) which is 14 sooo i believe either 7 or 2
<span>g(x)= 3x − 3
</span><span>g(−6)
g(-6) = 3(-6) - 3
g(-6) = -18 - 3
g(-6) = -21
The answer is -21.</span>